Shear-clinching of the high-strength aluminum alloy AA7075 with laser-assisted retrogression - Wiesenmayer, Sebastian; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2022)
Due to their extraordinarily high specific strength, aluminum alloys of the 7000 series are coming into focus of car manufacturers. In an aged state, the limited formability of the alloys poses a challenge for joining by forming processes, which are of particular importance for the realization of multi-material lightweight structures. The innovative shear-clinching technology has proven to be suitable for joining die-sided high-strength steels and punch-sided aluminum alloys. Yet, the process is limited by the formability of the upper joining partner. Due to the high strength of AA7075 in the artificially aged T6 temper, the material flow is obstructed during the joining sequence and failure occurs. The formability of the hardenable alloy can be enhanced by the performance of short-term heat treatment prior to joining. For this purpose, a laser is a suitable heat source, allowing the effective heating of small areas. Within this study, the influence of the temperature during the heat treatment with a diode laser on the material properties of AA7075 is investigated by uniaxial tensile tests and metallographic analyses. Moreover, the joinability of the alloy as well as the resulting joint formation and strength in dependence on the process control during the heat treatment are analyzed. Softening of the alloy enhances with increasing heat treatment temperatures. However, in comparison to the T6 temper, the ductility does not increase. For temperatures of 300 degrees C and higher, the joinability of AA7075 after the heat treatment is given. Still, for 300 degrees C cracks are initiated, compromising the joint quality. Despite the occurrence of cracks, the highest joint strength is achieved after a heat treatment at 300 degrees C, as for higher temperatures, the material's strength becomes distinctly lower.
CRIS-Team WoS Importer:2022-12-23